The Role of the Tourism Office in Tourism Development in Selayar Islands Regency - Jamaluddin; Padli, Ainur; Niswaty, Risma (Journal of Social Science and Economics (JOSSE), 2024)
The Role of the Tourism Office in Tourism Development in Selayar Islands Regency is an agency that plays an important role in developing or changing in terms of tourism in the region, especially in Selayar Islands Regency. This research method used is descriptive research located at the Selayar Islands Regency Tourism Office. For data collection carried out by researchers are observation, interviews and documentation. The data of the results of the study managed by researchers using Spradley data analysis techniques.From the results of this study can be used as a consideration and reference for making policies or future decisions in order to build and develop tourism in Selayar, so that tourist attraction objects can or can be managed properly by the tourism office, because many researchers previously they were only researchers about the income obtained by the agency Tourism in terms of attractions